Evaluation of the Mutagenic Potential of Artavol® Using the Ame’s Test - Oloro, Joseph; Kasazza, Kennedy; P’okello, Oscar Okidi; Mucunu, James M.; Maitho, Timothy E.; Ganafa, Amon A. (European Journal of Medicinal Plants, 2024)
Background: The worldwide increase in the use of herbal medicinal - products calls for their safety testing to protect the public from unintended hazardous effects. However, most are not tested, putting the public at risk. The modified Ames ISO test is a useful resource for determining the mutagenic potential of medicinal products and was used in this study to determine the safety of an herbal tea like Artavol®. Methods: This study used Ame's Modified ISO test to analyze aqueous extract of Artavol®, in a Level II biosafety cabinet. Artavol® was extracted using the infusion method 1,2, freeze dried, diluted to concentrations of 125µg, 250µg, and 500µg and used in the study. Mutagenicity was tested by culturing Salmonella typhimurium TA98 and TA100. Results were considered by observing colour change in the wells of the microtitre plates from purple to yellow indicating mutation. Valid results were determined by comparing negative and positive control plates after 3 days of incubation, with positive results showing a color change from purple to yellow. Results: Colour changes were not observed in all wells containing 125µg, 250µg, and 500µg of Artavol® up to day 3, while positive control showed color changes equivalent to 80% for TA98 and 70% for TA100. Conclusion: Aqueous extract of Artavol® is not mutagenic. Further safety test such as sub-chronic toxicity study ad teratogenicity studies are recommended to provide more safety data on the product.
Keywords: Artvol®; Mutagenicity; Ame’s test; Artemisia annua; Dihydroartemesinin-3-desoxy- and deoxyartemisinin; Cedrol